Pemanfaatan SMTP Client pada Sistem Absensi VB.Net - Adiguna, M A (Jurnal Teknologi dan Informasi (JATI), 2020)
Technological information innovations an important role on a system absentee at education institutions, at an institute of learning a small scale or great . In the study is done the use of smtp client on a system absentee in one of the course in Cikarang Bekasi District. The presence of instructors and learners of using e-mail notification can assist the agency in terms of efficiency, In the time , control as well as charge. The background problem of this research is because the attendance system at the course institute's output is a thermal paperoll printout. The purpose of this research is to optimize paper efficiency and optimize the use of information technology through a Gmail account. The research method used in this study uses action research and experiment which includes analysis of problems as well as the architecture used to solve problems. Application programming designed use of language visual studio 2010/VB.Net That is language BASIC (Beginner All purpose Source Instruction Code) with modules SMTPclient and MysqlClient. Limitation problem from this research, Sent notification to mail that is registered in a database in accordance record id of learners and instructors. As for his background How to efficiency paper and time to absentee and control of learners and instructors to be relied upon at a later date. The test results of the 5 dataset records tested in the application showed 100% working well. This research will be continued with a combination of sms gateway and machinery fingerprints and connected with information system of the agency, that information in accordance with criteria good information, that is accurate , relevant and timely.